FISCAL MULTIPLIERS DURING THE GLOBAL FINANCIAL CRISIS: FISCAL AND MONETARY INTERACTION MATTERS. (8th May 2014) - Pyun, Ju Hyun; Rhee, Dong‐Eun
<x xml:space="preserve">Abstract</x> This study investigates the fiscal multipliers of 21 Organization for Economic Co‐operation and Development countries during the global financial crisis using panel vector auto regression methodology. Our findings suggest that the 1‐year fiscal multiplier was greater than 1 during the crisis, whereas it was less than 1 before the crisis because of different fiscal and monetary interactions. The combination of expansionary monetary and fiscal policies during the crisis boosted gross domestic product more effectively through internal and external transmissions: investment crowding‐out was limited, and net exports were spurred by the policy interaction. In addition, our results are robust to various specifications. (JEL E61, E63, E65)